Perspektif Sistem Inovasi Dalam Konten Kebijakan Daerah Jawa Timur Bidang Iptek dan Inovasi Periode 2000-2011 - Prakoso Bhairawa Putera (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2012)
Regulatory regions as the object of attention of this study are discussed in the content published policies and provide regulation of science technology and innovation in the area. Policy in the area of this study is that the regulation of East Java Province. The method of this research is using the content analysis with frame of innovation system. The results revealed that 64% of science-technology and innovation policy period from 2000 to 2011 in the province of East Java has relevance and significance to the development (research), diffusion and utilization of technology in the area. Generally the regulations in East Java emphasis on institutional strengthening, and supporting of science-technology and innovation program.